2012
DOI: 10.4236/jct.2012.36136
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Involvement in Multiple Myeloma: A Case Report

Abstract: Purpose: To report a retro-orbital localization of Multiple Myeloma (MM) describing its treatment and clinical result. Case report: A 50-years-old male patient with Magnetic Resonance Imaging (MRI) evidence of a retro-orbital mass with exophthalmos, due to the pathological diagnosis of MM, was referred for Radiation Therapy (RT). Discussion: The orbital involvement in Multiple Myeloma is rare and few cases are reported in the literature. The treatment of choice is RT alone with a prescribed dose ranging betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This disease has an age-adjusted incidence of 4.7 cases per 100,000 populations 2 . It often occurs in adults, and the mean age at diagnosis is 70 years 3 . One of the most prominent features of this disorder is the presence of more than 10% clonal plasma cells in the bone marrow or biopsy associated with end-organ damage 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This disease has an age-adjusted incidence of 4.7 cases per 100,000 populations 2 . It often occurs in adults, and the mean age at diagnosis is 70 years 3 . One of the most prominent features of this disorder is the presence of more than 10% clonal plasma cells in the bone marrow or biopsy associated with end-organ damage 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Literature review identified a total of 111 previously reported cases in 68 articles regarding orbital involvement in patients with systemic MM (Table 2). 4,6-61…”
Section: Resultsmentioning
confidence: 99%